CUSTOMER RELATIONSHIP MANAGEMENT IN MAINTENING AND INCREASING THE NUMBER OF CUSTOMERS - Riyan Pradesyah; Winda Saputri (Proceeding International Seminar of Islamic Studies, 2022)
The development of financial institutions is currently experiencing a significant increase, this can be seen from the increase in the number of offices of financial institutions, especially in Islamic banking. This development is certainly a challenge for financial institutions, to maintain the customers they have. However, there are also many Islamic financial institutions, especially Islamic banks that have lost their customers for various reasons. In this study, it has a specific goal , namely to see whether Islamic banks have implemented Customer Relations Management in maintaining and increasing the number of their customers. The object of research in this research is Bank Sumut KCPsy Multatuli. The method used for the completion of the research is descriptive qualitative. The results obtained, that Bank SUMUT KCPSy has implemented Customer Relationship Management, namely in the dimensions of people, processes and technology, so that many customers feel comfortable with the services provided at Bank SUMUT KCPSy Multatuli.Keywords: Customer Relationship Management, Customers, Loyalty